1991
DOI: 10.7863/jum.1991.10.7.381
|View full text |Cite
|
Sign up to set email alerts
|

Automatic measurements of fetal long bones. A feasibility study.

Abstract: We investigated whether it would be possible for a computer to propose values for measurements com-· monly obtained (femur and humerus) during obstetrical sonography. ln this preliminary study, the images were scanned and analyzed off-line using morphological operators. The procedure described allowed us to measure the long bones and has a very high coefficient A n important part of obstetrical ultrasound is the measurement of a series of parameters that are used to assess gestational age and evaluate normalcy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 6 publications
0
10
0
2
Order By: Relevance
“…One of the first attempts to evaluate automatic fetal biometry was the study done by Thomas JG and coauthors in 1991 [10]. They investigated whether it would be possible for a computer to measure long bones of the fetus.…”
Section: Discussionmentioning
confidence: 99%
“…One of the first attempts to evaluate automatic fetal biometry was the study done by Thomas JG and coauthors in 1991 [10]. They investigated whether it would be possible for a computer to measure long bones of the fetus.…”
Section: Discussionmentioning
confidence: 99%
“…Automation of fetal biometry is one possible way to increase efficiency in the workflow while at the same time offering the potential for improved accuracy and reproducibility. The first attempt of fetal biometry automation was for FL measurement, over two decades ago. Recent work by Yazdi et al .…”
Section: Discussionmentioning
confidence: 99%
“…Automation of fetal biometry is one possible way to increase efficiency in the workflow while at the same time offering the potential for improved accuracy and reproducibility. The first attempt of fetal biometry automation was for FL measurement, over two decades ago 8 . Recent work by Yazdi et al has shown that automated measurements can reduce intraoperator variability and can therefore potentially be relied upon for reproducibility 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, automatic fetal biome- try may improve the efficiency of prenatal sonography. Previous studies demonstrated the feasibility of automated fetal biometric measurements 1,[7][8][9][10][11][12][13] and that this approach is both reliable and reproducible. 1 However, our study further demonstrates that the automatic biometric method is more efficient than the manual one in the setting of a busy ultrasound practice.…”
Section: Discussionmentioning
confidence: 99%